On the evolution of star forming galaxies : the metallicity of dwarfs and the effect of environment on local luminous IR galaxies - Tekola, Abiy G (Department of Astronomy, 2015)
This thesis, entitled "On evolution of star forming galaxies: the metallicity of dwarfs and the effect of environment on local luminous infrared galaxies" is divided into two main areas. First a detailed study of the environment and star formation relationship of local Luminous Infrared Galaxies (LIRGs), with infrared (IR) luminosity (LIR) between 1011L and 1011L, where L is solar luminosity was carried out. Secondly, a chemical abundance analysis was done on three Local Volume dwarf irregular galaxies. In the first part, various redshift surveys were used to quantify the environment around LIRGs. It was found that LIR 1011L is a remarkable luminosity point among IR galaxies.